Pemahaman Guru Bimbingan Konseling Tentang Nilai-nilai Religiusitas Islam dan Implementasinya dalam Bimbingan dan Konseling Kelompok - Cahyo Setiadi Ramadhan; Siti Bahiroh (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2021)
Counseling is helpful for adolescents to overcome their problems. A good counselor needs to know the background of the counselee. The counseling based on client's background will be more successful. Therefore it is necessary to practice Islamic guidance and counseling in high schools. In addition, counselors who handle Islamic guidance and counseling activities also need to have knowledge of Islamic values. So this research will examine the understanding of guidance and counseling teachers (BK teachers) regarding Islamic values and the application of these Islamic values in group guidance and counseling activities. The research was conducted in three Islamic-based high schools in the DIY urban area. The two schools studied were six-year boarding schools with students of the same sex. The approach of the research was qualitative approach and it’s data collection technique was in-depth interview. The results showed that the teacher of guidance and counseling has sufficient knowledge of Islamic values and the application of these values in Islamic guidance and counseling. The application of these values has been carried out in two forms. First, Islamic values become material in the guidance process. The second, Islamic values become a method of group guidance and counseling.